Upper Perené Arawak narratives of history, landscape, and ritual - Mihas, Elena (University of Nebraska Press, 2014)
"Published through the Recovering Languages and Literacies of the Americas initiative, supported by the Andrew W. Mellon Foundation. The rich storytelling traditions of the Ashéninka Perené Arawaks of eastern Peru are showcased in this bilingual collection of traditional narratives, ethnographic accounts, women's autobiographical stories, songs, chants, and ritual speeches. The Ashéninkas are located in the colonization frontier at the foot of the eastern Andes and the western fringe of the Amazonian jungle. Unfortunately, their language has a slim chance of surviving because only about three hundred fluent speakers remain. This volume collects and preserves the power and vitality of Ashéninka oral and linguistic traditions, as told by thirty members of the Native community. Upper Perene Arawak Narratives of History, Landscape, and Ritual covers a range of themes in the Ashéninka oral tradition, through genres such as myths, folk tales, autobiographical accounts, and ethnographic texts about customs and rituals, as well as songs, chants, and oratory. Transcribed and translated by a specialist in Ashéninka language varieties, Elena Mihas, and grounded in the actual performances of Asheninka speakers, this collection makes these stories available in English for the first time. Each original text in Ashéninka is accompanied by an English translation and each theme is introduced with an essay providing biographical, cultural, and linguistic information. The result is a masterful, authoritative, yet entertaining and provocative collection of oral literature that vividly testifies to the power of Ashéninka storytelling"--